2020
DOI: 10.1111/obr.13023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of body roundness index in predicting metabolic syndrome: A systematic review and meta‐analysis

Abstract: Body roundness index (BRI) is a new anthropometric index developed to predict both body fat and the percentage of visceral adipose tissue. Our aim was to investigate whether BRI is superior to traditional anthropometric indices in predicting metabolic syndrome (MetS). This systematic review and meta-analysis was conducted using Pubmed, Scopus and Web of Sciences databases. The estimated pooled areas under curve (AUCs) for BRI predicting MetS was higher than body mass index (BMI), waistto-hip ratio (WHR), body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 91 publications
4
72
0
5
Order By: Relevance
“…Meanwhile, a study with Polish population also showed that BRI had superior ability to predict metabolic syndrome [ 46 ]. Generally, BRI possesses a stable ability to predict cardiometabolic risk and metabolic syndrome even in different ethnic groups, and these results were well determined in our study [ 49 ]. Moreover, Chang et al [ 64 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Meanwhile, a study with Polish population also showed that BRI had superior ability to predict metabolic syndrome [ 46 ]. Generally, BRI possesses a stable ability to predict cardiometabolic risk and metabolic syndrome even in different ethnic groups, and these results were well determined in our study [ 49 ]. Moreover, Chang et al [ 64 ].…”
Section: Discussionsupporting
confidence: 69%
“…Body roundness index (BRI) was developed to predict both body fat and the percentage of visceral adipose tissue using WC in relation to height, which will estimate the shape of the human body figure as an ellipse [ 4 , 43 , 71 ]. BRI was generally used as an adipose indicator for determining the presence of hyperuricemia, arterial stiffness, CVD, diabetes, dyslipidemia, hypertension, and MetSy [ 7 , 46 , 49 , 51 , 67 , 68 ]. However, BRI was limited in predicting percentage of fat mass in athletes when compared with bio-impedance analysis or skinfold prediction [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a better predictor of body fat and the percentage of visceral tissue compared with traditional indicators, such as the BMI and WC [29]. The discriminatory power of the BRI in predicting MetS was similar to that of the WC and only slightly lower than that of the WHtR [30]. It was higher than that of the BMI and ABSI in both sexes.…”
Section: Introductionmentioning
confidence: 84%
“…Derived risk of excessive trunk fat was described in mid 1900s in the adult (21) stressing the body shape of the individuals. These risks were proven later by means of the association with T2D (22, 23), hyperuricemia (24), elevation of free T and MRI assessed abdominal fat distribution (25), with heart failure mid-range ejection fraction (26), or even with the vintage metabolic syndrome, this relationship was established by means of different waist circumference derived indexes (27). It is worth referring to the conclusions of Baton Rouge (28) after analyzing these varied equations, although in favor of the Waist circumference index, considered the indexes capacity for evaluating an individual person's health risks.…”
Section: Discussionmentioning
confidence: 99%